SOCIALLY CONSTRUCTED DEATH IN SHIRLEY JACKSON’S THE LOTTERY - Winarti; Hidayatulloh, Aris; SM, Syafrianto; Marginingsih; Setiawati, Beta; Wardhani, Evi Murti (PT Akselerasi Karya Mandiri, 2025)
Death as a literary theme has long served as a reflection on life, existence, and cultural values. This study investigates how social traditions legitimize inherited violence in Shirley Jackson's The Lottery, arguing that the story represents death not as a natural or inevitable occurrence, but as a culturally sanctioned and ideologically constructed event. Employing a qualitative content analysis grounded in structuralist and deconstructive theory, the research examines how meaning is produced through recurring symbols—the black box, stones, and ritual—revealing the mechanisms by which violence becomes normalized within communal structures. By integrating structuralist attention to narrative systems with deconstruction’s critique of fixed meaning, this study contributes to literary scholarship by demonstrating how Jackson’s story functions as a critique of social complicity and ritualized violence. Theoretically, the paper advances discussions on the intersection of ideology, tradition, and power in literary representations of death, offering insights into how fiction can expose the constructed nature of social norms and the ethical consequences of collective obedience.